The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3389/fpsyt.2021.704330
|View full text |Cite
|
Sign up to set email alerts
|

Antianhedonic Effect of Repeated Ketamine Infusions in Patients With Treatment Resistant Depression

Abstract: Anhedonia constitutes one of the main symptoms of depressive episode. It correlates with suicidality and significantly effects the quality of patient's lives. Available treatments are not sufficient against this group of symptoms. Ketamine is a novel, rapid acting strategy for treatment resistant depression. Here we report the change in symptoms of anhedonia measured by Snaith-Hamilton Pleasure Scale as an effect of eight ketamine infusions as an add-on treatment in 42 patients with treatment resistant depress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 34 publications
(37 reference statements)
2
18
0
Order By: Relevance
“…Relevant to the understanding of ketamine’s efficacy in patients with MDD, ketamine infusion into the NAc protected marmosets from the anhedonic-like effects of scACC-25 overactivation for more than 1 week. This parallels results reported previously in humans, and more recently in marmosets, after systemic ketamine administration ( 8 , 21 , 28 , 29 ). Identification of the neural circuit mechanism through which ketamine acts to mediate its anti-anhedonic effects is critical for developing more effective long-term treatments for patients with MDD.…”
Section: Discussionsupporting
confidence: 91%
“…Relevant to the understanding of ketamine’s efficacy in patients with MDD, ketamine infusion into the NAc protected marmosets from the anhedonic-like effects of scACC-25 overactivation for more than 1 week. This parallels results reported previously in humans, and more recently in marmosets, after systemic ketamine administration ( 8 , 21 , 28 , 29 ). Identification of the neural circuit mechanism through which ketamine acts to mediate its anti-anhedonic effects is critical for developing more effective long-term treatments for patients with MDD.…”
Section: Discussionsupporting
confidence: 91%
“…Use of BZDs among patients with major depressive disorder was found to be associated with increased anhedonia but not anxiety or depression symptom levels (perhaps because BZDs mitigated anxiety) and anhedonia was the strongest predictor of BZD use in that study ( 133 ). A recent clinical study of repeated ketamine infusions in 42 patients with treatment-resistant major depression found that ketamine (an NMDA receptor antagonist) significantly reduced anhedonia (SHAPS scores) after each infusion but only among the subgroup of patients who did not use BZDs ( 134 ). Although the present study was not designed to examine BZD withdrawal and anhedonia, we did not find any significant difference in anhedonia scores between BZD misusers and never-misusers, nor between participants whose urine samples tested BZD-positive vs. BZD-negative.…”
Section: Discussionmentioning
confidence: 99%
“…This study has several limitations. First, the model used in this study and others, in which ketamine is used to induce the manic phase, is valid, but the accuracy of this assessment has not been discussed in past years, although the aims of previous studies were to explore new methods for the improvement of treatment effects in patients with treatment-resistant depression and to rapidly reduce suicide attempts due to severe depressive symptoms in BP (Valvassori et al, 2019 ; Kim and Monteggia, 2020 ; McIntyre et al, 2020 ; Chen et al, 2021 ; Dean et al, 2021 ; Keilp et al, 2021 ; Magalhães et al, 2021 ; Nikayin and Sanacora, 2021 ; Wilkowska et al, 2021 ). A reviewer of this article led us to rethink the validity of the use of ketamine to induce the manic phase when studying BP (a physiopathological process), as drug-induced manic behavior may have different underlying mechanisms, Strictly speaking, a ketamine-induced manic phase can only represent such a phase induced by antidepressants, which is usually observed in clinical practice.…”
Section: Discussionmentioning
confidence: 99%